IMPROVE COLLIGATIVE PROPERTIES SKILLS AND PROBLEM SOLVING ABILITY OF SMA NEGERI 1 BABALAN CLASS XII STUDENTS USING MODEL PROBLEM BASED LEARNING (PBL) (International Journal of Education and Literature, 2023)
This study was to find out how the application of the Problem Based Learning (PBL) model to the topic of Colligative Properties in the science program at SMA Negeri 1 Babalan Class XII academic year 2021–2022 would increase students' problem-solving skills and learning activities. Three cycles of action research were used in this study. 32 SMA Negeri 1 Babalan students from the first semester of the academic year 2021–2022 served as the study's subjects. The findings came from watching students engage in learning activities and testing their capacity to solve problems at each stage of the Cycle. The results demonstrated that 1) college students' problem-solving skills improved by implementing the PBL model on the Colligative Properties subject, with average values from Cycles I to II and III of 56, 77, and 87, respectively, while the percentage of classical completion from Cycles I to II and III was 44%, 62,5%, and 87%, with gains from Cycles I to II of 0,083 and from Cycles II to II equal to 0,35; 2). Applying the PBL model to the topic of Colligative Properties resulted in an increase in the students' learning activities, with an average value of 75 in sufficient criteria, 77 in sufficient criteria, and 85 in good criteria from Cycle I to Cycle II and Cycle III, respectively.